Response of organic manures on post harvest and soil nutrient restoration on cauliflower production - Basnet, Manoj; Shakya, Shanta Man; Baral, Bandhu Raj (Journal of Agriculture and Environment, 2018)
This study was conducted at Ilam Municipality-2, Nepal to determine the response of organic manures on post harvest and nutrient restorative effect of cauliflower. Five manures, viz., bansoon, mustard oil cake, poultry manure, farmyard manure, and vermi-compost were evaluated. The postharvest losses, vitamin C content and soil nutrient restorative behavior were significantly highest with vermi-compost as compared to other manures. The maximum vitamin C content of 10.92 mg/100 gm was found with vermi-compost whereas the lowest of 9.66 mg/100 gm was found at farmyard manure. Moreover, the physiological losses were found to be least with vermi compost and the most with bansoon manure. Moreover, the restorative properties i.e. pH, N,P,K and organic %age were found to be significantly highest with vermi-compost as compared to other organic manures. This study concludes that vermi compost increases vitamin C content, postharvest longevity and improvement of physical and chemical properties of the soil.